2013
DOI: 10.1166/jnn.2013.7370
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Fumaric Acid Functionalized AgCl/Titania Nanocomposite with Enhanced Antibacterial Activity

Abstract: Silver based antimicrobial agents with TiO2 as a host support (AgCl/TiO2) are increasingly being evaluated for disinfection and therapeutic applications. In this work TiO2 supported silver chloride nanocomposites were synthesized and functionalized with fumaric acid. X-ray diffraction results showed that the TiO2 was in anatase phase and AgCI was in the cubic chalcoargyrite phase. The functionalization was confirmed by FTIR analysis. The fumaric acid functionalized AgCl/TiO2 (Fu-AgCl/TiO2) showed uniform parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
3
2
0
Order By: Relevance
“…This occurs due to amino group carries a positive charge and is present in AgNPcol [40,41] ( Figure 1D). The hydrodynamic diameter of the nanoparticles was between 64.34 nm and 81.76 nm and PDI value was between [42] showed PDI value of 0.47, which was very close to the result obtained from this study, although other PDI values were also reported [43][44][45]. The value of PDI is one of the major parameters used for selecting a low-polydispersity solution for the subsequent cell viability test.…”
Section: Resultssupporting
confidence: 88%
“…This occurs due to amino group carries a positive charge and is present in AgNPcol [40,41] ( Figure 1D). The hydrodynamic diameter of the nanoparticles was between 64.34 nm and 81.76 nm and PDI value was between [42] showed PDI value of 0.47, which was very close to the result obtained from this study, although other PDI values were also reported [43][44][45]. The value of PDI is one of the major parameters used for selecting a low-polydispersity solution for the subsequent cell viability test.…”
Section: Resultssupporting
confidence: 88%
“…The hydrodynamic diameter of the nanoparticles was between 64.34 nm and 81.76 nm and PDI value was between 0.40 and 0.77. The AgNPs associated with titanium dioxide synthesized by Desai and Kowshik [ 42 ] showed PDI value of 0.47, which was very close to the result obtained from this study, although other PDI values were also reported [ 43 – 45 ]. The value of PDI is one of the major parameters used for selecting a low-polydispersity solution for the subsequent cell viability test.…”
Section: Resultssupporting
confidence: 88%
“…These studies attributed the increase in antimicrobial susceptibility to modifications of TiO 2 with natural elements and non-metallic compounds [45,46,54,55]. Our MIC results are consistent with previous findings reporting MIC against various G-positive and G-negative bacteria in the similar range [45,[56][57][58][59] while other studies reported the MIC against MRSA to be much higher (7.0-13.0 mg/ml) [60,61]. Our study showed that the UV light on TiO 2 had no significant changes in the reduction rate.…”
Section: Discussionsupporting
confidence: 92%